Analisis Faktor- Faktor yang Mempengaruhi Take Home Pay Dosen di Kota Makassar - Sri Astuty; Abdul Hakim (Seminar Nasional LP2M UNM, 2019)
This study aims to examine the direct and indirect effects between the main workload, additional work hours, age, and education level on take home pay through productivity. The novelty targeted is the development of a lecturer welfare improvement model. The long-term goals and specific targets expected from this research are to study and develop a model for improving the welfare of lecturers in South Sulawesi Province. The results of the study can contribute to the development of science in the field of microeconomics, especially labor supply. The method used in achieving research objectives based on population characteristics, the number of existing population is 900, then a sample of 100 lecturers was drawn. Sampling at each university based on the level of further education or based on PTN. Sampling is done using the cluster method and stratified random sampling, which is based on the type of University and serves PTN as the main work. Where in this study estimating the magnitude of direct and indirect effects will be carried out by linear regression analysis in a simultaneous model (Structural Equation Model, SEM) using the AMOS program. The expected outcome in this study is National Procedings.